Some aspects of modernization of the far east (japanese) sociality: experience for Ukraine - Мозгова, Т. А. (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
This article analyzes the new geopolitical challenges facing modern Ukraine, which today is an important strategic partner between Eastand West. The future of Ukraine – is the prospect of transregional cooperation with countries of the Far East.